Creating valuable relationships with third-party logistics (3PL) providers: A multiple-case study - Eric Owusu Darko; Ilias Vlachos (Logistics, 2022)
Background: Logistics service outsourcing in recent years has influenced the evolution of third-party logistics (3PL) providers across the globe. The study explored the evolving services of 3PLs and relational factors that influence the relationship with their customers. Methods: Qualitative research and multiple case studies from four different industries were used. Semi-structured interviews were adopted. Results: The findings show that aside from logistics and warehousing the customer expects 3PLs to create value through more decision-making responsibilities, such as managing the customer's relationship with 3PLs, and customised services that will make them competitive. Furthermore, the results showed that to achieve relationship performance, trust must be collaborative from the start, which increases information sharing and leads to an improved relationship performance. Conclusions: Consistent performance increases commitments from both partners. Implications, limitations and future research suggestions are provided.
Keywords: 650; business relationships; case study; decision making; supply chain; third-party logistics; value creation